Structural diversity offsets the mortality risk of tree species richness while enhancing productivity in subtropical plantations - Yuli Liao; Jian Wang; Hui Wang; Shirong Liu; Yeming You; Xueman Huang; Ji Zeng; Xiuli Tong; Jihuang Xu (Forest Ecology and Management, 2026)

Respiratory viral sepsis: rethinking fluid resuscitation and antibiotic stewardship - Dong Liu; Mengwei Yan; Di He; Zai Wang; Yeming Wang; Bin Cao (Science China Life Sciences, 2026)

Optical effects of thin regolith coatings on rock surfaces: Laboratory measurements and radiative transfer modeling - Yan Zhuang; Hao Zhang; Pierre Beck; Sylvain Douté; Bernard Schmitt; Yeming Liu (Icarus, 2026)

First record of Fraxinoxylon (Oleaceae) from the Miocene of Sihong, Jiangsu Province, China, and its palaeogeographic implication - Yanbin Zhu; Ya Li; Xiaohua Zhou; Yanfeng Song; Kai Liu; Ren Jiang; Yeming Cheng (Review of Palaeobotany and Palynology, 2026)

Divergent Responses to 16 Years Near-Natural Transformation: Forest-Type Specific Regulation of Soil Microbial Communities in Subtropical Coniferous Plantations - Angang Ming; Jian Chen; Weiei Shu; Xiaoguo Zhou; Yuying Liang; Huilin Min; Guangyu Xue; Dongjing Sun; Yi Tao; Yeming You; Yingzhuo Xi; Shirong Liu (Journal of Soil Science and Plant Nutrition, 2026)

WTAP mediated m6A methylation modulates retinal photoreceptor function via facilitating of REEP6, PDE6B and RDH12 translation - Kuanxiang Sun; Lin Zhang; Wenjing Liu; Can Chen; Jiajie He; Jinrui Cai; Xiaoyan Jiang; Yeming Yang; Zhenglin Yang; Xianjun Zhu (Science China Life Sciences, 2026)

Investigation of the hydrodynamic characteristics of the underwater propulsion pump blade based on a bionic strategy - Miao Jin; Haoran Liu; Guoyong Jin; Fangming Zhou; Yeming Lu; Xiaofang Wang (Ocean Engineering, 2025)

Changes in the proteome of yolk granules induced by freezing: Label-free proteomics and molecular dynamics simulation analysis - Yeming Liu; Yanqing Wan; Jing Sun; Yuanyuan Shan (Food Research International, 2025)

Maotai Town's peculiarity creates unmatched sauce-flavor liquor - A review - Shuang Han; Youcui Yang; Yeming Zhou; Qing He; Mingqian Liu; Xiao Zou (Food and Humanity, 2025)

Endophytic colonization via Cordyceps cateniannulata induces a growth-enhancing effect and increases the resistance of tomato plants against Tetranychus urticae (Koch) - Jingqiang Guan; Jing Liu; Jianyu Gou; Zhongshun Xu; Yeming Zhou; Xiao Zou (Crop Protection, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Multi-objective evolutionary neural architecture search for network intrusion detection - Qiuzhen Lin; Zhihao Liu; Yeming Yang; Ka-Chun Wong; Yahui Lu; Jianqiang Li (Swarm and Evolutionary Computation, 2024)

PM2.5 induces developmental neurotoxicity in cortical organoids - Yuqing Han; Zhenjie Yu; Yue Chen; Xiaoyu Guo; Yeming Liu; Hao Zhang; Zhiqing Li; Liqun Chen (Environmental Pollution, 2024)

Geological investigation of the lunar Apollo basin: From surface composition to interior structure - Dijun Guo; Yeming Bao; Yang Liu; Xing Wu; Yuchen Xu; Yazhou Yang; Feng Zhang; Bradley Jolliff; Shuai Li; Zhenxing Zhao; Liying Huang; Jianzhong Liu; et al. (Earth and Planetary Science Letters, 2024)

Fine particulate matter concentration prediction based on hybrid convolutional network with aggregated local and global spatiotemporal information: A case study in Beijing and Chongqing - Qiaolin Zeng; Yang Cao; Meng Fan; Liangfu Chen; Hao Zhu; Lihui Wang; Yeming Li; Sizhu Liu (Atmospheric Environment, 2024)

Cerebral ischemic injury after transcatheter aortic valve replacement in patients with pure aortic regurgitation - Xianbao Liu; Hanyi Dai; Jiaqi Fan; Dao Zhou; Gangjie Zhu; Abuduwufuer Yidilisi; Jun Chen; Yeming Xu; Lihan Wang; Jian’an Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Differential effects of forest-floor litter and roots on soil organic carbon formation in a temperate oak forest - Yuxue Zhang; Zuoxin Tang; Yeming You; Xiaowei Guo; Chuanjing Wu; Shirong Liu; Osbert Jianxin Sun (Soil Biology and Biochemistry, 2023)

Comparison of aroma active compounds in cold- and hot-pressed walnut oil by comprehensive two-dimensional gas chromatography-olfactory-mass spectrometry and headspace-gas chromatography-ion mobility spectrometry - Ying Xu; Shuang Bi; Xiaoyuan Niu; Yeming Chen; Ye Liu; Qi Zhou (Food Research International, 2023)

The ER membrane protein complex subunit Emc3 controls angiogenesis via the FZD4/WNT signaling axis - Mu Yang; Shujin Li; Wenjing Liu; Xiao Li; Yunqi He; Yeming Yang; Kuanxiang Sun; Lin Zhang; Wanli Tian; Lixin Duan; Huafu Chen; Dezhong Yao; et al. (Science China Life Sciences, 2021)

Study of the Operating Characteristics for the High-Speed Water Jet Pump Installed on the Underwater Vehicle with Different Cruising Speeds - Yeming Lu; Haoran Liu; Xiaofang Wang; Hui Wang (Journal of Marine Science and Engineering, 2021)
Due to the higher propulsive efficiency, lesser vibration, and better maneuverability, the water jet pump is widely applied to high-speed underwater vehicles. By taking a newly developed water jet pump system as the object, the corresponding underwater vehicle’s operating characteristics affected by different cruising speeds (15.43, 30.86, and 52.47 m/s) were investigated. The steady results reply that the cruising speed increase will result in the decline of the overall performances comprised of the head, the efficiency, the thrust, and the power. While, by using different analyzing methods, the unsteady results are listed as follows: (1) The energy loss theory denotes that the increasing cruising speed promoted the kinetic energy diffusion from the Reynolds stress and viscous stress and depress the turbulent kinetic energy production and the viscous dissipation. (2) The statistical PLS method reveals that the tip load effect on the leakage flow becomes weaker when the cruising speed becomes larger, while the effect from the scraping pressure has a completely opposite trend. (3) Further unsteady analysis implies that the increasing cruising speed makes the pressure pulsation larger and makes the radial force, the axial force, and the cloudy cavity size smaller.

Microbial community and associated enzymes activity influence soil carbon chemical composition in Eucalyptus urophylla plantation with mixing N2-fixing species in subtropical China - Xueman Huang; Shirong Liu; Yeming You; Yuanguang Wen; Hui Wang; Jingxin Wang (Plant and Soil, 2017)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.